2023
DOI: 10.1007/s10278-023-00893-y
|View full text |Cite
|
Sign up to set email alerts
|

A Deep Learning Image Reconstruction Algorithm for Improving Image Quality and Hepatic Lesion Detectability in Abdominal Dual-Energy Computed Tomography: Preliminary Results

Bingqian Chu,
Lu Gan,
Yi Shen
et al.

Abstract: This study aimed to compare the performance of deep learning image reconstruction (DLIR) and adaptive statistical iterative reconstruction-Veo (ASIR-V) in improving image quality and diagnostic performance using virtual monochromatic spectral images in abdominal dual-energy computed tomography (DECT). Sixty-two patients [mean age ± standard deviation (SD): 56 years ± 13; 30 men] who underwent abdominal DECT were prospectively included in this study. The 70-keV DECT images in the portal phase were reconstructed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…DL may extrapolate information outside the field of measurement of the second source-detector pair [66,67]. AI reduces image noise and improves DECT imaging quality [68][69][70][71]. Moreover, current material decomposition techniques suffer from excessive image noise and artifacts due to the dose limit in CT scanning and the noise magnification of the material decomposition process.…”
Section: The Future Of Dect Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…DL may extrapolate information outside the field of measurement of the second source-detector pair [66,67]. AI reduces image noise and improves DECT imaging quality [68][69][70][71]. Moreover, current material decomposition techniques suffer from excessive image noise and artifacts due to the dose limit in CT scanning and the noise magnification of the material decomposition process.…”
Section: The Future Of Dect Imagingmentioning
confidence: 99%
“…DLR provides better noise containment for low keV images and AI techniques have been demonstrated that may improve material decomposition performance and detectability of low iodine concentrations [69,71,72]. Additionally, in clinical practice, AI has also shown to be useful in tumor detection, characterization, staging, and prognosis [70,[73][74][75][76].…”
Section: The Future Of Dect Imagingmentioning
confidence: 99%